2018
DOI: 10.1515/sjpain-2017-0140
|View full text |Cite
|
Sign up to set email alerts
|

Low dose ketamine versus morphine for acute severe vaso occlusive pain in children: a randomized controlled trial

Abstract: AbstractBackground and aims:Acute pain episodes associated with sickle cell disease (SCD) are very difficult to manage effectively. Opioid tolerance and side effects have been major roadblocks in our ability to provide these patients with adequate pain relief. Ketamine is cheap, widely safe, readily available drug, with analgesic effects at sub-anesthetic doses and has been used in wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 37 publications
2
40
0
1
Order By: Relevance
“…Ketamine, a noncompetitive NMDA receptor antagonist, may have the potential to modulate opioid-induced hyperalgesia through impaired sensitization of spinal neurons to nociceptive stimuli, and may therefore reduce neuropathic pain. Lubega et al [18] performed a randomized controlled trial in pediatric patients with SCD and found that 1 mg/kg of IV ketamine was not inferior to 0.1 mg/kg morphine in terms of maximum improvement in NPRS scores among SCD children with acute severe VOC pain.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine, a noncompetitive NMDA receptor antagonist, may have the potential to modulate opioid-induced hyperalgesia through impaired sensitization of spinal neurons to nociceptive stimuli, and may therefore reduce neuropathic pain. Lubega et al [18] performed a randomized controlled trial in pediatric patients with SCD and found that 1 mg/kg of IV ketamine was not inferior to 0.1 mg/kg morphine in terms of maximum improvement in NPRS scores among SCD children with acute severe VOC pain.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] The analgesic efficacy of ketamine has also been replicated in children of various ages and disease profiles. [48][49][50]…”
Section: Clinical Applications Of Ketaminementioning
confidence: 99%
“…A case report describes the use of low‐dose ketamine infusion in a young man suffering an acute pain crisis, in treatment with several drugs including methadone . A randomized controlled trial conducted on paediatric patients demonstrated comparable NRS score reductions with intravenous low‐dose ketamine versus morphine …”
Section: What Is Newmentioning
confidence: 99%
“…The main side effects ascribed to ketamine are fatigue, headaches, dizziness, feeling of unreality, generalized discomfort, changes in hearing, changes in mood, hallucinations and changes in vision. As previously demonstrated, low‐dose infusion is the preferred mode of administration in order to minimize such side effects.…”
Section: What Is Newmentioning
confidence: 99%